Prospective of SNCA in nervous system diseases. Issue 1 (28th March 2017) - Jia, Chao; Liu, Wei
Abstract : Synuclein alpha (SNCA), a protein isolated from the Pacific Electric sturgeon, is well‐known for its distribution in the nuclei of neurons and could charge the organ choline. Immunohistochemical staining showed that synuclein were distributed in the synaptic terminal, also expressed in the postsynaptic membrane and synaptic cleft, involving in the synthesis and release of neurotransmitter. The structure of synuclein contains synuclein alpha, beta and gamma. Alpha and beta synuclein are related to the neural degenerative diseases, including Alzheimer's disease and Parkinson's disease, gamma synuclein is involved in breast cancer, bladder cancer and oral squamous cell carcinoma. SNCA is the main component of the amyloid plaques and Lewy bodies during the primary neuronal degeneration, therefore it has become the star of the nervous system diseases. Here, we reviewed recent literatures about SNCA and investigate the prospective of SNCA in the nervous system diseases.